OPTIMASI PENJADWALAN MATAKULIAH MENGGUNAKAN ALGORITMA GENETIKA DI FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS HASYIM ASY’ARI - Ilham Zulhardani, Muhammad; Sujatmiko, Bambang; Faizah, Arbiati (Inovate, 2020)
Scheduling is a process schedule or entering data into a schedule. In academic sector, scheduling is used toschedule course subjects. In the Faculty of Information Technology Hasyim Asy’ari University schedule is madefor the study programs for Bachelor of Computer Science (S1), Bachelor of Information System (S1), and AssociateDegree of Information Management (D3). However there are 4 students academic years in each degree or studyprogram. The room provided is only 5 rooms and lecture time starting from Saturday to Wednesday with lecturehours starting at 08.00 a.m until 6 p.m. Furthermore the scheduling still made by using Microsoft Excel. The casesoften cause a schedule crash. Therefore it is necessary to use an application of scheduling optimation in order tominimize the schedule crash. Optimization problems often solved using genetics algorithm. Genetics algorithm ispretty good to used in scheduling the course subjects because it is able to finish multi-criteria cases and multiobjectivesmodeledasbiologyandevolution.Theresultresearchshowsthattheschedulethathasbeenmadehas anerrorvalueof21,6%withfitnessvalueof0,05andthenumberofschedulecrashis19crashes.Thefitness valueisresultedfromthecombinationofgeneticsparameterthatisthepopulationsize is 100, crossover 0,7,mutation 0,3 and generation 500. The schedule settlement cannot reach a perfect value because in this case theclassroom number is this scheduling is very limited, that is only 5 classrooms. Keywords: Genetics Algorithm, Courses, Optimation, Scheduling